СПОРТ ЖАМОАЛАРИДА ПСИХОЛОГИК ХИЗМАТ КЎРСАТИШНИНГ БАЪЗИ ЖИҲАТЛАРИ - Арзымбетов, Т.Т. (SCIENCE and SOCIETY, 2022)
This article analyzes the research conducted in our country on the study of psychological services in the field. Also, the relevance of research on the problem of psychological services in sports teams on the basis of modern approaches is scientifically based.
Keywords: psychological service; sports teams; community psychology; social personality; psychological literacy; socio-psychological climate; sports psychologists; psychological protection; national mentality; sports activities